ANALYSIS OF ORDER OF STRESS SINGULARITY AT A VERTEX IN 3D TRANSVERSELY ISOTROPIC PIEZOELECTRIC DISSIMILAR BONDED JOINTS (Journal of Mechanical Engineering, 2014)
The order of singularity near the vertex of bonded joints is one of the main factors responsible fordebonding under mechanical or thermal loading. The distribution of stress singularity field near the vertex ofbonded joints is very important to maintain the reliability of intelligent materials. In this paper, order of stresssingularity at vertex in 3D transversely isotropic piezoelectric dissimilar bonded joints is analyzed. Eigenanalysis based on FEM is used for stress singularity field analysis of piezoelectric bonded joints. The eigenequation is used for calculating the order of stress singularity, and the angular function. The numerical resultshows that the angular functions have large value near the interface edge than the inner portion of the joint.Therefore, there is a possibility to debond and delamination may occur at the interface edge of the piezoelectricbonded joints due to the higher stress and electric displacement concentration at the free edge.DOI: http://dx.doi.org/10.3329/jme.v44i1.19490